1995
DOI: 10.1161/01.cir.91.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Transesophageal Echocardiography for the Diagnosis and Management of Nonobstructive Thrombosis of Mechanical Mitral Valve Prosthesis

Abstract: Transesophageal echocardiography appears to be a reliable method to diagnose thrombi on a mechanical mitral valve prosthesis, even when transthoracic Doppler echocardiographic parameters appear to be normal. Transesophageal echo assessment of thrombus size may be helpful in deciding whether a patient with mitral prosthesis should be treated by anticoagulation, thrombolysis, or valve rereplacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Transesophageal echocardiography (TEE) is currently the test of choice for evaluating the mechanism of prosthetic valve obstruction (23) and allows the quantitation of thrombus burden (24,25). Whether TEE is helpful in identifying structural or functional parameters that can risk-stratify patients undergoing thrombolysis has not been previously investigated.…”
mentioning
confidence: 99%
“…Transesophageal echocardiography (TEE) is currently the test of choice for evaluating the mechanism of prosthetic valve obstruction (23) and allows the quantitation of thrombus burden (24,25). Whether TEE is helpful in identifying structural or functional parameters that can risk-stratify patients undergoing thrombolysis has not been previously investigated.…”
mentioning
confidence: 99%
“…A number of recent studies with transesophageal echocardiography (TEE) have identified a high incidence of nonobstructive thrombi (NOT) in the early postoperative period after mechanical mitral valve replacement (MMVR) (1)(2)(3)(4)(5). Such phenomena are known to increase morbidity and mortality and are often the consequence of inadequate anticoagulant therapy in the highly unstable period after surgery (3,6,7).…”
mentioning
confidence: 99%
“…Fibrinolytic therapy for a left-sided prosthetic valve obstructed by thrombus is associated with significant risks (cerebral emboli in 12% to 15% of cases) and is often ineffective. Fibrinolytic therapy in such patients is reserved for those in whom surgical intervention carries a high risk and those with contraindications to surgery (573)(574)(575)(576)(577)(578)(579)(580).…”
Section: Antithrombotic Therapy In Patients Who Need Cardiac Cathetermentioning
confidence: 99%